(512) Credit Planning in the Socialist Economy تخطيط الائتمان في الاقتصاد الاشتراكي - Fedorowicz, Zdzislaw (INP, 2024)
Discusses the financial balance sheet plan for banks within the context of economic planning, explaining how to estimate the increase in loans granted by banks and the increase in monetary assets and deposits. Credit planning requires estimating the demand for credit based on the financial activity of different economic units. The estimation of monetary resources should be based on the proper organization of savings and reserves. The need for credit increases when the value of goods and services exceeds available monetary revenue. The credit plan is prepared annually and quarterly in Polish planning practice, detailing the distribution of credits granted to socialist enterprises and the private sector. The plan also covers changes in monetary deposits across different accounts and circulating money.